INNOVATIVE PLAY-BASED LEARNING FOR COGNITIVE AND SOCIAL-EMOTIONAL DEVELOPMENT IN PRESCHOOLERS - Fozilova Odina Nabiyevna, (Scholar Express Journal, 2025)
Play-based learning is a crucial approach in early childhood education, fostering both cognitive and social-emotional development. This study explores the impact of structured play on preschoolers' problem-solving abilities, memory retention, attention span, and emotional regulation. A comparative analysis between traditional and play-based learning environments revealed that children engaged in guided play exhibited significant improvements in cognitive functions and social adaptability. Future research should focus on optimizing the balance between traditional and digital play-based methodologies to maximize developmental outcomes.
Keywords: Play-based learning; cognitive development; social-emotional skills